Functional Ultrasound Imaging of Cocaine Induced Brain-Wide Neurovascular Response - Shaoyuan Yan; Nan Huang; Yusheng Tong; Yousheng Shu; Qiumin Le; Dean Ta; Kailiang Xu (NeuroImage)
Extensive studies have reported that cocaine can lead to potent reduction in cerebral blood flow. However, the mechanisms of the cocaine's impact on the neural and vascular system of brain in temporal and spatial aspects remain elusive. Functional ultrasound (fUS) is a novel neurovascular imaging modality acclaimed for its deep penetration, superior spatiotemporal resolution, and high sensitivity to small blood flow dynamics. This study aims to use fUS technique to characterize the regional differences in hemodynamic responses to acute cocaine administration. The CBV responses revealed that the cortex and ventral tegmental area (VTA) were the regions most significantly affected by cocaine. In addition, electroencephalography (EEG) was also utilized to assess the neural activities in the cortex and VTA. In the cortex, the observed CBV changes responded more rapidly to cocaine than local field potential (LFP) activities, indicating that prior to acting on the central nervous system, cocaine may first affect the peripheral nervous system, accelerating heart rate and increasing cardiac output. Both hemodynamic and neural responses showed opposing patterns between cortical and VTA brain regions. Based on these observations, we proposed a two-stage hypothesis to explain acute cocaine's multifaceted impact on the brain. This study underscores the efficacy of fUS as a powerful and sensitive tool for tracking cocaine-induced hemodynamic changes and enhances our understanding of cocaine's effects on the neurovascular system.